Investigation on ultra high strength slurry infiltrated multiscale fibre reinforced concrete. (2020) - Mohan, A.; Karthika, Saravana; Ajith, J.; dhal, Lenin; Tholkapiyan, M.
Abstract: The demand of high quality of strength mingled with the superior standards and durability leads to development of Slurry infiltrated fibrous reinforced concrete. It is a comparatively new material and can be treated as a special type of fibre reinforced concrete (FRC). It differs from normal FRC in three aspects – the fibre content, Cementitious matrix and method of production. It is made by infiltrating cement slurry into a number of bed fibres preplaced and packed tightly in the moulds. Because of its high strength, excellent energy absorption, ample stiffness and many other good properties, precast SIFCON slabs will have a wide range of structural engineering applications where high energy based elements are required. The main objective of this study is to determine the mechanical properties of slurry infiltrated fibrous concrete with multi-scale of steel fibre. The aim of present investigation is to study the flexural behaviour of SIFCON. The steel fibres used for this study is crimped type of two different length 12 and 30 mm with 8% by volume. Development of ultrahigh strength of more than 100 MPa compressive strength slurry for the preparation of SIFCON. The work on this study evaluates the mechanical properties of the SIFCON like compressive, flexural.